Awareness of the Installation the Lightning Protection System (LPS) by Using Structural Bonding Method in Malaysia - Abdul Rahim, Mustaqqim; Shahidan, Shahiron; Abdul Ghani, Abdul Naser; Che Munaaim, Muhammad Arkam; Md. Ghazaly, Zuhayr; Ismail, Syahirah; Ismail, Isham (EDP Sciences, 2017)
Structural Bonding Method (SBM) is one type of Lightning Protection System (LPS), design to protect human, structures, contents inside structures, electrical equipment, transmission lines and other from the lightning flash. Besides, SBM is a standard LPS that comply with technical standards or codes of practice or called as conventional Lightning Protection System. In order to know the level of the Awareness of the Installation LPS by using SBM in the building among Civil Engineering Consultants, conducting survey need to be done. This paper presents the Research Design and Research Strategy in conducting the survey. It is explaining about the way before conducting the survey which are determine the population of sample (Consultant Company at Northern Region Area), samples of respondents (Civil Engineer at Consultant Office with the number of sample is 40), data collecting process, structure of the questionnaire form and the way in analysis the data. After the analysis the data, the result of the level of awareness in the Installation of LPS by using SBM are consider as moderate level.